If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13i + 7 = 2i + -9 Reorder the terms: 7 + 13i = 2i + -9 Reorder the terms: 7 + 13i = -9 + 2i Solving 7 + 13i = -9 + 2i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2i' to each side of the equation. 7 + 13i + -2i = -9 + 2i + -2i Combine like terms: 13i + -2i = 11i 7 + 11i = -9 + 2i + -2i Combine like terms: 2i + -2i = 0 7 + 11i = -9 + 0 7 + 11i = -9 Add '-7' to each side of the equation. 7 + -7 + 11i = -9 + -7 Combine like terms: 7 + -7 = 0 0 + 11i = -9 + -7 11i = -9 + -7 Combine like terms: -9 + -7 = -16 11i = -16 Divide each side by '11'. i = -1.454545455 Simplifying i = -1.454545455
| 594=18b+72 | | 2(x+2)=6x+1-4x+3 | | -6w+10=-10-8w | | x(5)=315 | | 2z+4z+2+z+10=z+2+20 | | 9y+5=15y+7 | | s^3+2s^2+12s-40=0 | | 120-80y=-3y+9 | | 4+4y+2=-2 | | 46/n=117 | | N^2-12n=32 | | 4a(5)3= | | 2x-5=2x+18 | | m-11=15-6b | | -6x+-6x= | | t=1.25h-10 | | -1-7x=36x+(-7-x) | | -6z+6=6-6z | | 0.2v=1.2 | | 2(y-1)+6y=10 | | 25-6x=-65 | | 7x-(3x+13)=23 | | 21-1/24(3)=14-1/24(2x) | | 1.1-t+2.2=5.9 | | 10x^3-9x^2-9x= | | 0=-6y+6y | | 2n=3(n+9) | | 21-1/24(3x)=14-(2x) | | (4a(5))3= | | 1-2f=-2f+1 | | 3r/6 | | x^2-16x+128=0 |